2011
DOI: 10.1111/j.1471-6712.2010.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivators and barriers to exercise among adults with a high risk of type 2 diabetes – a qualitative study

Abstract: Adults with high risk of T2D experienced many individually meaningful motivators. They experienced few barriers to exercise and highlighted the motivators. Thus, we present that they had a positive attitude towards increasing exercise during participation to counselling. The results can be used when developing counselling methods because they provide concrete content for counselling discussion such as importance of work-related factors, family exercise, time management skills and social support for regular exe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(111 citation statements)
references
References 48 publications
7
91
0
1
Order By: Relevance
“…These findings are in accordance with a qualitative study by Korkiakangas et al. (47), which indicated that adults with high risk of type 2 diabetes experienced few barriers to exercise and highlighted the motivators. However, it should be noted that although the participants in our study reported an overall positive level of exercise expectancies, as well as a low negative value related to exercise, they generally reported low exercise activity.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with a qualitative study by Korkiakangas et al. (47), which indicated that adults with high risk of type 2 diabetes experienced few barriers to exercise and highlighted the motivators. However, it should be noted that although the participants in our study reported an overall positive level of exercise expectancies, as well as a low negative value related to exercise, they generally reported low exercise activity.…”
Section: Discussionsupporting
confidence: 92%
“…Improved health, the desire to have more energy, and personal appearance have been found to be motivators for improved diet and exercise habits in other studies (Chang, Nitzke, Guilford, Adair, & Hazard, 2008;Korkiakangas et al, 2010). The measure of these four constructs provided insight into the residents of Appalachian Kentucky counties.…”
Section: Discussionmentioning
confidence: 89%
“…They found improvements on several peak and sub-maximal cardiorespiratory parameters but no changes in fasting blood glucose or glycosylated hemoglobin post-training. Similar indirect or adjacent health function improvements, based on physical exercise/training regimes, have been indicated (Hamer et al 2009a, b;Hankonen et al 2010;Korkiakangas et al 2010). Significantly, Larose et al (2010) have found that the benefits of physical exercise in conditions of type 2 diabetes mellitus were much more advantageous in elder than in younger populations.…”
Section: Exercise and Diabetes Liabilitymentioning
confidence: 91%